The Effectiveness of Cooperative Integrated Reading and Composition (CIRC) Technique in Teaching Reading on Narrative Text - Farah Yunita; Abdul Muin; Fitri Hilmiyati (Loquen, 2017)
This research investigates the effectiveness of Cooperative Integrated Reading and Composition (CIRC) technique in teaching reading on narrative text. This research conducted based on the problems: 1) How is the students’ reading comprehension on narrative text before using CIRC technique at the second grade of MTs Al-Khairiyah Pipitan? 2) How apply is CIRC technique to students’ reading comprehension on narrative text at the second grade of MTs Al-Khairiyah Pipitan? 3) How effective is CIRC technique in teaching reading on narrative text at the second grade of MTs Al-Khairiyah Pipitan? To answer the questions, the writer collects data from 60 students spread into two classes, one class as experimental class and another one is as control class. the writer takes the sample from VIII E as experimental class and VIII F as control class. the experimental class was taught using Cooperative Integrated Reading and Composition (CIRC) technique and control class taught using Grammar Translation Method (GTM). Since the research used experimental research, the data is gathered through pre-test and post-test. The result of the reseach shows that the value tobservasition is 3,77 the writer compared it with ttable both in degree significance 5% and 1%. Therefore, to:tt = 3,77 > 2,00 in degree significance 5% and to:tt = 3,77 > 2,66 in degree of significance 1%. The statistic hypothesis states that if to is hugher than tt, it shows that Ha (alternative hypothesis) of the result is accepted and Ho (null hypothesis) is rejected. It means that significance is the effectiveness of CIRC technique in teaching reading on narrative text.